Use of Online Medical Records to Support Medical Decision Making: A Cross-Sectional Study of US Adults. Issue 9 (2nd September 2021) - Langford, Aisha T.; Orellana, Kerli; Buderer, Nancy
Abstract : The use of online medical records has increased over time and may enhance patient involvement in medical decisions. We explored sociodemographic, medical condition, and digital health correlates of using online medical records to support medical decision making. Cross-sectional data from the 2019 Health Information National Trends Survey (HINTS 5, Cycle 3, N = 5438) were analyzed. Final analyses included participants who accessed their online medical records within 12 months and had complete data for all variables (n = 1807). The outcome was, "In the past 12 months have you used your online medical record to help you make a decision about how to treat an illness or condition (yes/no)?" Univariate and multivariate odds ratios and 95% confidence intervals were calculated. Multivariately, the odds of using online medical records to support medical decision making were significantly higher for individuals who (a) used online medical records to securely send messages to health care providers, (b) used a smartphone health app to access their online medical records, (c) had online medical records that contained clinical notes, (d) reported that online medical records were useful for monitoring health, and (e) self-identified as African American, Asian, or "Other." Online medical records may support medical decision making depending on the context.